BISNIS MULTI LEVEL MARKETING (E-COMERCE): PANDANGAN DAN SISTEM INFORMASI AKUNTANSI (SYARIAH) DI INDONESIA - Rohmatul Umah, Shoffi; Putri Lestari, Anggita; Nur Habib, Asifi Antoni; Masyfu’i, Moh. Wildan; Latifah, Eny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
The purpose of this study was to determine the views and accounting information systems in Multi Level Marketing (E-Commerce) business in Indonesia. The research method is qualitative with a literary approach that uses data sources from reference books, articles and other sources in order to find complete information and in accordance with the data listed. The results of the study show that there are views of the Multi Level Marketing business that punish mubah and some that forbid it. The reason for the Multi Level Marketing business is not allowed, namely there is gharar, violating the principles of the transaction contract, and the motivation for the transaction contract is a bonus, not goods and the career path is determined by how quickly you join as a member, depending on the package taken. Meanwhile, the Multi-Level Marketing business accounting system is a reference for making decisions regarding rewards that will be given to members with good performance with automatic distribution according to incoming data and has been confirmed by the part in charge.